Feasibility of using circumferential space for railway bridges - Alexey A. Loktev; Irina V. Shishkina (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. The most popular design solutions for bridge crossings on railways are either girder structures with a suffciently high cross-sections located below the train load application level, or trusses whose height depends on the span length and more often than not far exceeds the height of the railway clearance. This motivates to consider design solutions that utilise the space immediately around the transport dimension without increasing the cross-sectional height from below or above the plane of application of the dynamic load. Since the cab exerts a variable and highly cyclic load, control of compressive and tensile stresses will be required at the top and bottom of the spanwise cross-section. The work attempts to justify the use of the geometric space immediately adjacent to the contour of the vehicles in the design of the transverse profile of the span structure.Materials and Methods. Authors determined the stress deformation of the beam span by analysing the bending moments and extreme normal stresses to select concrete reinforcement or steel beam geometry. The evaluation criteria are normal stresses, which could be compressive or tensile depending on the location of the wheel pairs on the impact lines.Results. The paper analyses the existing approaches to evaluate the inclusion of cross-sectional elements of a girder structure located above the plane of wheel load application (e.g. ballast bed sides). The analysis provides graphical relationships for the moment of inertia of a cross-section with different geometries, which is actually a target function that relates the  geometric dimensions of the girder span along and across the cab movement to the principal stresses and determines the optimum position of the load application surface relative to the top and bottom of the cross-section.Discussion and Conclusion. This approach is suitable for both open H-beam sections and box sections with sides currently widely used in the design of bridge crossings for high-speed railway lines. A significant effect could be achieved due to higher span sides and the location of the lower shelf of the cross-section box. Multi-level interchanges at the same span dimensions allow the proposed design solutions to reduce the distance between the levels of mobile load application.